Glial imaging during synapse remodeling at the neuromuscular junction - Zuo, Yi (2009)
Glia are an indispensable structural and functional component of the synapse. They modulate synaptic transmission and also play important roles in synapse formation and maintenance. The vertebrate neuromuscular junction (NMJ) is a classic model synapse. Due to its large size, simplicity and accessibility, the NMJ has contributed greatly to our understanding of synapse development and organization. In the past decade, the NMJ has also emerged as an effective model for studying glia–synapse interactions, in part due to the development of various labeling techniques that permit NMJs and associated Schwann cells (the glia at NMJs) to be visualized in vitro and in vivo. These approaches have demonstrated that Schwann cells are actively involved in synapse remodeling both during early development and in post-injury reinnervation. In vivo imaging has also recently been combined with serial section transmission electron microscopic (ssTEM) reconstruction to directly examine the ultrastructural organization of remodeling NMJs. In this review, we focus on the anatomical studies of Schwann cell dynamics and their roles in formation, maturation and remodeling of vertebrate NMJs using the highest temporal and spatial resolution methods currently available.